Investigation of Compressive Strength and Energy Absorption of Cylinder Corrugated Sandwich Structures with Different Geometric Configurations - İlyas Bozkurt (Firat University Journal of Experimental and Computational Engineering, 2025)
The aim of this study is to numerically investigate and compare the compressive strength and energy absorption of CFRP composite cylinder sandwich structures with five different geometric configurations. The crushing performances (Peak crushing force (PCF), Mean crushing force (MCF), Crushing force efficiency (CFE), energy absorption (EA) and specific energy absorption (SEA)) of the composite cylinder for different core configurations and the failure types were determined. Compression analyses were performed in LS DYNA finite element program using MAT-54 material model with progressive failure analysis based on the combination of Hashin failure criterion, Cohesive Zone Model (CZM) and Bilinear traction-separation law. Among the five different specimens in the study, the highest PCF value was Trapeozidal with axial corrugated core while the lowest was Arc shaped with circular core. Axial arc shaped core was the sandwich structure with the highest SEA value, while circular sinusoidal corrugated core was the sandwich structure with the lowest SEA value. Between axial core and circular core, the CFE value of the sinusoidal core specimen was determined to be the highest. It was observed that the effect of core structure on the deformation behavior of sandwich structures was high.